USING SNOWBALL THROWING TO IMPROVE STUDENTS’ LITERAL READING COMPREHENSION AT SMPN 4 BONTONOMPO - Syahrir, Nur Ilmi Septia; Munir, Munir; Korompot, Chairil Anwar (Universitas Negeri Makassar, 2024)
This research aims to find out does the use of the snowball-throwing technique improves students’ literal reading comprehension. This research used a quantitative method with a pre-experimental design with instruments, namely literal reading comprehension questions. The population of this study is all grade 9 in SMPN 49 Makassar with a sample of 19 students of class 9.A. The data was collected through a pre-test and post-test, namely the pretest was carried out before the application of the snowball-throwing technique, and the post-test was carried out after the application of the snowball-throwing technique. The data was analyzed using the t-test at a significant level of 0.05 and from the results of the analysis obtained probability data (sig 2-tailed) 0.00 which means lower than the significant data level of 0.05 (0.00 <0.05). This study shows that H0 is rejected and HI is accepted. It can be concluded that the use of the snowball-throwing technique improved students’ literal reading comprehension at SMPN 4 Bontonompo.